Habitual Sleep, Social Jetlag, and Reaction Time in Youths With Delayed Sleep–Wake Phase Disorder. A Case–Control Study - Saxvig, Ingvild West; Wilhelmsen-Langeland, Ane; Pallesen, Ståle; Nordhus, Inger Hilde; Vedaa, Øystein; Bjorvatn, Bjørn (Frontiers in Psychology, 2019)
The aim of this study was to explore habitual sleep, social jetlag and day-to-day variations in sleep (measured as intra-individual standard deviation, ISD) in youths with delayed sleep-wake phase disorder (DSWPD), as compared to healthy controls. We also aimed to investigate time of day effects in performance. The sample comprised 40 youths with DSWPD (70.0% female, mean age 20.7 ± 3.1 years) and 21 healthy controls (71.4% female, mean age 21.2 ± 2.2 years). Subjective and objective sleep were measured over seven days on a habitual sleep schedule by sleep diary and actigraphy recordings. Performance was tested twice with a 12-hour interval (22:00 in the evening and 10:00 the following morning) using a simple, 10-minute sustained reaction time test. The results showed later sleep timing in the DSWPD group compared to the controls, but sleep duration, social jetlag and ISD in sleep timing did not differ between the groups. Still, participants with DSWPD reported longer sleep onset latency and poorer sleep efficiency, sleep quality and daytime functioning, as well as larger ISD in sleep onset latency, sleep duration and sleep efficiency. The groups had similar evening performances on the reaction time test, but the DSWPD group performed poorer (slower with more lapses) than the controls in the morning. The poor morning performance in the DSWPD group likely reflects the combined impact of sleep curtailment and circadian variations in performance (synchrony effect), and importantly illustrates the challenges individuals with DSWPD face when trying to adhere to early morning obligations.